Mobile application for safflower technology transfer: Mobile application for safflower technology transfer - P MADHURI; N MUKTA; K ANJANI; P PADMAVATHI; P S SRINIVAS; R D PRASAD; S V RAMANA RAO (Journal of Oilseeds Research, 2020)
Information and communication technologies brought significant change in agriculture development. Amongthe ICTs mobile technologies has better access to provide more information to the stakeholders. Towards this direction for effective technology transfer of safflower, an Andrioid based mobile application “ICARIIOR Safflower” mobile APP was developed at ICAR-IIOR to provide information on the safflower technologies to the stake holders. The information on different aspects of safflower viz., General information, Agronomic Practices, Preferred cultivars, Cropping systems, Insect pests, Diseases, AICRP centres and Commodity markets was compiled and categorised into major chapters with sub-topics within each. This APP supports English language and is available in Google play store.